River flooding as a driver of polygon dynamics: modern vegetation data and a millennial peat record from Anabar River lowlands (Arctic Siberia) - Zibulski, Romy; Herzschuh, Ulrike; Pestryakova, L. A.; Wolter, Juliane; Müller, Stefanie; Schilling, Nadine; Wetterich, Sebastian; Schirrmeister, Lutz; Tian, Fang (Biogeosciences, 2013)
The spatial and temporal variability of a low-centred polygon on the eastern floodplain area of the lower Anabar River (72.070° N, 113.921° E; northern Yakutia, Siberia) has been investigated using a multi-method approach. The present-day vegetation in each square metre was analysed, revealing a community of Larix, shrubby Betula, and Salix on the polygon rim, a dominance of Carex and Andromeda polifolia in the rim-to-pond transition zone, and a predominantly monospecific Scorpidium scorpioides coverage within the pond. The total organic carbon (TOC) content, TOC / TN (total nitrogen) ratio, grain size, vascular plant macrofossils, moss remains, diatoms, and pollen were analysed for two vertical sections and a sediment core from a transect across the polygon. Radiocarbon dating indicates that the formation of the polygon started at least 1500 yr ago; the general positions of the pond and rim have not changed since that time. Two types of pond vegetation were identified, indicating two contrasting development stages of the polygon. The first was a well-established moss association, dominated by submerged or floating Scorpidium scorpioides and/or Drepanocladus spp. and overgrown by epiphytic diatoms such as Tabellaria flocculosa and Eunotia taxa. This stage coincides temporally with a period in which the polygon was only drained by lateral subsurface water flow, as indicated by mixed grain sizes. A different moss association occurred during times of repeated river flooding (indicated by homogeneous medium-grained sand that probably accumulated during the annual spring snowmelt), characterized by an abundance of Meesia triquetra and a dominance of benthic diatoms (e.g. Navicula vulpina), indicative of a relatively high pH and a high tolerance of disturbance. A comparison of the local polygon vegetation (inferred from moss and macrofossil spectra) with the regional vegetation (inferred from pollen spectra) indicated that the moss association with Scorpidium scorpioides became established during relatively favourable ...